Smart Trends in Computing and Communications Proceedings of SmartCom 2024, Volume 1 - Senjyu, Tomonobu; So–In, Chakchai; Joshi, Amit (Lecture Notes in Networks and Systems, 2024)
XVII, 518 p. 206 illus., 152 illus. in color.